1)18ху-6х^2=6х(3у-2х)
2)15а^6-3а^4=3а^4(5а^2-1)
3)4(х-у)+с(х-у)=(х-у)(4+с)
11-(x+1)²≥x
11-x²-2x-1≥x
x²+3x-10≤0
x²+3x-10=0 D=49 √D=7
x₁=2 x₂=-5
(x-2)(x+5)≤0
-∞+-5___-2++∞ ⇒
ответ: x∈[-5;2]
(2x-8)²-4x*(2x-8)≥0
(2x-8)(2x-8-4x)≥0
(2x-8)(-2x-8)≥0
-(2x-8)*(2x+8)≥0 |÷(-1)
4x²-64≤0 |÷4
x²-16≤0
(x-4)(x+4)≤0
-∞+-4-4++∞ ⇒
ответ: x∈[-4;4].
x*(x+5)-2>4x
x²+5x-2-4x>0
x²+x-2>0
x²+x-2=0 D=9 √D=3
x₁=1 x₂=-2 ⇒
(x-1)(x+2)>0
-∞+-2-1++∞ ⇒
ответ: x∈(-∞-2)U(1;+∞).
(1/3)*x²+3x+6<0 |×3
x²+9x+18<0
x²+9x+18=0 D=9 √D=3
x₁=-3 x₂=-6 ⇒
(x+3)(x+6)<0
-∞+-6--3++∞ ⇒
ответ: x∈(-6;-3).
x>(x²/2)-4x+5¹/₂
x>(x²/2)-4x+11/2 |×2
2x>x²-8x+11
x²-10x+11<0
x²-10x+11=0 D=56 √D=√56
x₁=5-√14 x₂=5+√14
-∞+5-√14-5+√14++∞ ⇒
ответ: x∈(5-√14;5+√14).
18xy -6x² = 6х( 3у - х)
15a^6 -3a⁴ = 3a⁴(5а² - 1)
4x-4y+cx-cy = 4(х-у) + с(х-у) = (х-у)(4+с)